Bangkit: mengungkap resiliensi pada remaja drop out - Aura Fajar Kumalasari; Arthur Huwae (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
Teenagers are faced with many challenges that can have an impact on life, including an impact on the school environment. Problems faced by adolescents can result in dropping out. Adolescents who are faced with dropping out are at high risk of various physical and mental health problems, as well as at high risk of committing crimes up to suicide attempts. Individuals who have dropped out need to be revived from this condition, one of which is by developing resilience. The purpose of this research is to look at the resilience of adolescents who have dropped out in terms of resilience aspects and factors. The method used is qualitative with a descriptive case study approach. Collecting data using observation, interviews, and documents. Data analysis was carried out in four stages, namely domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The results of the study show that adolescents who have dropped out have developed resilience as a continuous process that is constantly changing